Case Report: A rare case of chest wall thyroid carcinosarcoma - Wang, Tianyun; Sun, Chengpeng; Wang, Yuxi; Zhao, Chunmei; Guo, Minmin; Wang, Xiaofang; Kui, Xiang; Wang, Yan (Frontiers in Oncology, 2026)
Thyroid carcinosarcoma (TCS) is a rare and aggressive malignant tumor, typically reported as a primary thyroid neoplasm. Here, we present an unusual case of TCS occurring in the chest wall. The patient was a 66-year-old woman with a history of papillary thyroid carcinoma (PTC) diagnosed 12 years prior. She received two courses of radioactive iodine (RAI) therapy (200 mCi and 150 mCi) five years ago for metastatic disease in cervical lymph nodes and lungs. Four years after completing RAI treatment, she presented with a progressively enlarging left chest wall mass, which was surgically resected and pathologically confirmed as TCS. This report details the patient’s clinical course and explores the temporal and topographic association between the development of TCS and the prior RAI therapy.